Letter (copy) : Voluntary industrial aid - Citrine, Walter, 1887-1983
036-0032-001 ALSO SENT TO: Amal.Soc. of WOODCUTTING MACHINISTS WMC/WJB/AC/708 International 7th May, 1937. Mr. [Luke Fawcett, President,] G Hicks, M.P., Secretary Amalgamated Union of Building Trade Workers, "The Builders", Crescent Lane, S.W. 4. Dear Mr. [Fawcett,] Hicks, VOLUNTARY INDUSTRIAL AID. With reference to your letter of 20th April last, I shall be pleased to hear from you the views of your Executive Council as to the proposals for giving voluntary labour on behalf of the Spanish workers. It is of course understood that any such voluntary service will be done on an absolutely non-profit and non-trading basis. We have had replies from other Unions, but before coming to a definite decision wish to know the opinion of your members. Yours faithfully, General Secretary. 292/946/36/32